Teaching about hegemony : race, class and democracy in the 21st century - Orlowski, Paul, 1957- (Dordrecht ; New York : Springer, 2011)
'Political progressives in Canada and the United States are deeply concerned by the manner in which their countries treat their poor. They are dismayed at the dismantling of the social welfare state, the weakening of public education systems and the grotesque and ever-growing inequality of wealth. To remedy this problem, citizens need to be more aware of how political ideology influences attitudes and actions, and they need to better comprehend the effects of hegemonic discourses in the corporate media and school curriculum. This book informs educators how to develop context-specific pedagogy that will help achieve a more enlightened citizenry and, as a result, a stronger democracy. Teaching about Hegemony: Race, Class and Democracy in the 21st Century promotes a progressive agenda for teaching that is rooted in critical pedagogy, it explains why ideological critique is necessary in raising political consciousness, it deconstructs white, middle-class hegemony in the formal school curriculum, and it examines corporate media and school curriculum as hegemonic devices. It also covers recent theory and research about race, class and democracy and how best to teach about these topics. Combining theory and sociological research with pedagogical approaches and classroom narratives, this book is fundamental for educators interested in developing a politically conscious, progressive and active citizenry hungry for a stronger civil society.'--Publisher's website.
An introduction. So what does hegemony mean? -- Mostly theory : ideology, discourse, hegemony, and the curriculum. What's ideology got to do with it? -- The power of discourse, of course! -- The purpose of schooling: ideology in the formal and'enacted' curriculum -- Less theory, more applications and practice: deconstructing racial and class discourses for a stronger democracy. Teaching about race and racism in our past and present -- Social class: the forgotten identity marker in social studies education -- Liberal discourses about aboriginal students-a case study of power blindness -- Ideology, democracy, and the'good' citizen -- Neoliberalism: Laissez-faire revisited -- Some final reflections: dare the schools to teach for a fair social order.
Includes bibliographical references and index.
Keywords: Critical pedagogy -- North America; Progressive education -- North America; Popular education -- North America; Hegemony -- Study and teaching -- North America; Bildungspolitik; 2; Neoliberalismus